Personalized Medicine in Pharmacy: Revolutionizing Patient Care Through Precision Drugs - Karlita, Nita (JHN: Journal of Health and Nursing, 2024)
Personalized medicine has emerged as a groundbreaking approach in pharmacy, aiming to tailor drug therapy based on individual genetic profiles, environmental factors, and lifestyle variations. This article explores the integration of precision medicine into pharmaceutical care and its profound impact on therapeutic outcomes. Through a systematic review of relevant literature and case studies, the findings demonstrate that pharmacogenomics significantly improves drug efficacy, reduces adverse drug reactions, and empowers pharmacists to participate actively in patient-specific treatment decisions. Despite its numerous advantages, the implementation of personalized medicine faces challenges including cost barriers, limited genetic literacy among pharmacists, ethical concerns, and global disparities in access. Technological innovations such as artificial intelligence, electronic health records, and clinical decision support systems are gradually enabling wider adoption of personalized care models. The article concludes with strategic recommendations aimed at enhancing pharmacist education, establishing regulatory frameworks, and promoting interdisciplinary collaboration to advance the practice of precision pharmacy. Personalized medicine represents not only a shift in clinical methodology but also a redefinition of the pharmacist's role in delivering safe, effective, and individualized healthcare.